KEJAHATAN PENIPUAN DENGAN MODUS INVESTASI ILEGAL DALAM PERSPEKTIF KRIMINOLOGI - Simatupang, Aliza Yohana; Shodiq, Shodiq; Basuki, Basuki (SINERGI : Jurnal Riset Ilmiah, 2026)
The increasing incidence of fraud crimes employing illegal investment schemes has developed alongside changes in social, economic, and technological structures in modern society. These crimes demonstrate patterns of abuse of trust and manipulation of social relations carried out systematically and repeatedly. This research focuses on examining fraud crimes involving illegal investment schemes from a criminological perspective and on analyzing law enforcement responses to such offenses.  The analysis is conducted using criminological theories and theories of law enforcement. This research employs normative legal research aimed at obtaining relevant data related to the research problems. The data used consist of secondary data in the form of primary, secondary, and tertiary legal materials, supported by primary data as a complement to the secondary legal materials. Data analysis is conducted using qualitative juridical analysis.  The findings indicate that illegal investment fraud constitutes a form of modern economic crime carried out in a planned manner through the abuse of trust and manipulation of social relations. Law enforcement in this context remains predominantly legalistic and formalistic and has not fully positioned law as an instrument to serve human interests and protect victims of crime. This study suggests that law enforcement authorities should view illegal investment fraud as a systemic and organized economic crime, thereby necessitating stronger criminological analysis to dismantle criminal networks. Furthermore, law enforcement efforts should be directed not only toward the punishment of perpetrators but also toward the protection of victims and the recovery of their losses through strengthened regulation of digital investment activities and the adoption of more progressive, preventive, and adaptive approaches.